ANALYSIS OF INCREASING OF CONCRETE COMPRESSION STRENGTH TO CONCRETE’S AGE DUE TO ADDING ADMIXTURE OF SIKAMENT-163 - Turu’allo, Gidion (MEKTEK, 2007)
This research presents the study about the effects of adding admixture Sikament-163 to the increasing of concrete compression strength vs. concrete’s age. The percentage of Sikament-163, which is added in concrete mixture, is 1.0 % by cement weight. This research was conducted using each 25 of test specimens for normal concrete and added Sikament-163 concrete with the same slump. The tests were conducted when the concrete’s age reached 3, 7, 14, 21 and 28 days. The results of test show that the concrete compression strength of the concrete using Sikament-163 increase 13.5 % average above the normal concrete for each concrete’s age. This is because the adding admixture Sikament-163 into concrete mixture can reduce the volume of used water for the same slump; therefore, concrete, which was produced, is more compact and more strength.